LOCALISMS IN THE EAST-STEPPE DIALECTS OF DONETSK REGION - Клименко, Наталія (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
Despite the wide study of the lexical system of Ukrainian newly created dialects, the East-Steppe dialects of Donetsk region still need to be researched in detail. One of the urgent tasks of Ukrainian dialectology is to analyze the indigenous lexis that has already been recorded, since unsystematic dialectal phenomena should also be studied for a complete description of the composition and changes in the lexical system of Ukrainian dialects. At present, there are no works devoted to the study of dialectal lexis of indigenous nature of the Ukrainian East-steppe dialects. The analysis of endemic lexis in the newly created Ukrainian dialects, which include the Eaststeppe dialects of Donetsk region, seems to be of particular relevance, as it helps to determine the connections between the newly formed dialects and the mother dialects, i.e. the neighboring Russian and Ukrainian ones, as well as to find out the main trends in development and the specifics of the newly created Ukrainian dialects. The purpose of the article is to analyze the localisms in the lexical system of the East-steppe dialects of Donetsk region. Methods. Descriptive. Results. Local lexis functioning in the dialects under study is conditioned not only by emergence of new words for designating specific local realities, but also by preservation of names which are ancient by origin and have darkened, non-transparent motivation. The latter can function as relict names of a dialect, as well as to be local names of modern concepts, which is associated with the features of the realia plan and the structure of the lexis of the newly created dialects. Partially the indigenous names are the innovations characteristic of the contact dialects areas, with a transparent motivation and word-formation models which are common for the newly created 89 dialects. Some local names arose due to specific phonetic and word-formation processes in the dialects under study. A significant group of names of indigenous nature comprise East- steppe nomens, formed as a result of changing the semantic structure of words. Originality. The lexis of indigenous character has been the subject of special studies in Ukrainian linguistics for a long time. However, there is still no special research devoted to the analysis of endemism as language units of local distribution on the material of the Ukrainian East-steppe dialects. Conclusion. Further study of the local nomens of the East- steppe dialects will not only clarify the specifics and areal behavior of the newly created dialects of the Ukrainian dialect continuum, but also determine the nominative and isotropic processes in the Ukrainian dialectal language.